Activity Evaluation of CoMo Nanoparticles Supported on Meso-microporous Composites in Dibenzothiophene Hydrodesulphurization - Nastaran Parsafard; Mohammad Hasan Peyrovi; Zahra Mohammadian; Niloofar Atashi (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
CoMo-supported mesoporous catalysts were synthesized by 50 wt% of HZSM-5 and 50 wt% of FSM-16, KIT-6, and MCM-48. These catalysts were prepared by the wet-impregnation method and pre-sulfided with CS2. The catalytic performance was evaluated for HDS reaction of dibenzothiophene over a temperature range of 250-400 °C in a micro fixed-bed reactor under atmospheric pressure. The supported CoMo bimetallic catalysts were characterized by XRD, XRF, FT-IR, N2 adsorption-desorption, and SEM. The CoMo/KIT-6/HZSM-5 indicate higher activity than other catalysts at 400 °C for dibenzothiophene hydrodesulphurization. Also, the best selectivity to cyclohexylbenzene (CHB) is related to CoMo/FSM-16/HZSM-5. The activation energy was also calculated for all prepared catalysts for the conversions of less than 10%; according to which, the activation energy for CoMo/KIT-6/HZSM-5 is less than other catalysts (~21 kJ/mol) which can be related to the appropriate pore size and high surface area of the support. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).